Assessing the Impact of Climate Change on Crop Production in Katsina State, Nigeria - Abba Yakubu Abdullah; Tijjani Abu Rimi; Mohammed Saidu Mohammed (Research Advances and Challenges in Agricultural Sciences Vol. 8, 2024)
Aims: The present study aimed to assess the impact of climate change on crop production in Katsina State, Nigeria. Background: Climate change impacts food sufficiency and livelihoods thereby frightening and touching millions of smallholder farmers in sub-Saharan Africa. Most of the states in the northern part of the country that were acknowledged to be the major food producers of Nigeria, faced the aforementioned climatic threats, which made them vulnerable and highly susceptible to climate change that became a menace to the nation’s food security. Methodology: This research adopted a cross-sectional survey design and the data for the study were collected using a questionnaire to the respondents. Data was gathered via questionnaires administered to farmers,’ employing Village and Block Extension Agents as enumerators. A multi-stage sampling technique was employed. The first stage involved classifying the state into three ecological zones. The second stage comprises a random selection of three villages from each 34 LGAs to give 102 villages. The third stage was accomplished, based on the lists of farmers, 26,589 frames, obtained from Katsina State Agricultural and Rural Development Authority, twelve thousand farmers were selected proportionately for the study, using a systematic random sampling technique. Results: The results indicated that male and youthful age dominate production, respectively. A large proportion fall within formal to post-primary education and, more than two-thirds had no extension contact and the highest obtained income from #300,001- #450,000. The findings on the impact of climate change on crop production showed that 648,300 hectares of cultivated land and 633,950 tons of crops were lost. The analysis further unveiled that among the three ecological zones of the state, Sahel Savannah had the most devastating effect of losses, at both cultivated land of 292,200 hectares and crop yield of 267,100 tons. More so, the result portrayed that amongst the assorted crops produced in the area, millet, groundnut, cowpea, and sorghum were the major crops affected by climate change scourge. Conclusion: It is imperative to take immediate action to prevent climate change since it is a serious threat with increasingly catastrophic manifestations. It is advised that farmers learn about the effects of climate change on agricultural output and that research facilities produce more seeds that are situation-specific. To enable early planning by other stakeholders, the government should guarantee reliable climate estimation. Farmers need to be educated by the extension agents on the need to abide by recommended practices in climate resilience agronomic practices and other mitigation means of curtailing the danger posed by climate change. Efforts should be intensified on dry season farming by building more irrigation infrastructure to complement wet season production.